A Study on the Origin of Indian Instrumental Music - Dr. Soumya.S (International Journal of Engineering and Management Research, 2022)
Music is found everywhere in this beautiful world. As every art needs a strong medium to express its apparatus and uniqueness, similarly, a musical instrument is a medium to express the musical ‘Nada’, which has significance all over the world. Instrumental Music has an important place in Indian Music. It is one of the threefold aspects of Music (Vocal Music, Instrumental Music, and Dance) also known as ‘Sangeet’ in Indian Music. The Instrumental Music is known as "Vadhya Sangeet".From the beginning of Instrumental Music, two components are very important- Instrument and the Instrumentalist or Instrument player (Artist). It is impossible to manifest music art in the deficiency of any one of the component mentioned above. Music is known as a direct way to convey feelings from ancient times. The present study assesses the origin of Indian musical instrumentation.